1994
DOI: 10.1002/1097-0142(19940801)74:3<978::aid-cncr2820740330>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Total body irradiation and prednimustine in chronic lymphocytic leukemia and low grade non-Hodgkin's lymphomas. A 9-year experience at a single institution

Abstract: Background. The efficacy and toxicity of total body irradiation (TBI) in patients with chronic lymphocytic leukemia (CLL) and low grade non‐Hodgkin's lymphomas (NHL) were evaluated. Methods. Between January 1984 and September 1992, 81 consecutive patients, 40 affected with CLL and 41 with low grade NHL, with symptomatic Stage III and IV disease, were treated with TBI followed by prednimustine. TBI was given with a 6 MV linear accelerator, applying two opposite alternating fields, including total body, with two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The molecular remissions occurred while patients received immunosuppression for treatment of GVHD, indicating that powerful GVT responses were generated and continued even with control of other GVHD manifestations. Although low-dose TBI given with or without alkylating agents may induce remissions in some patients with untreated CLL and NHL, 52,53 it has not been reported that low-dose TBI can induce CRs and molecular remissions in patients with chemotherapyresistant CLL, and in particular after failure of previous fludarabinecontaining regimens. Similarly, although low-dose TBI may have transient suppressive effects on CML, even high-dose myeloablative regimens (at least 1200 cGy TBI plus intensive chemotherapy) are by themselves often incapable of providing sustained disease control, as indicated by the frequent relapses observed after using T-cell-depleted allografts.…”
Section: Org Frommentioning
confidence: 99%
“…The molecular remissions occurred while patients received immunosuppression for treatment of GVHD, indicating that powerful GVT responses were generated and continued even with control of other GVHD manifestations. Although low-dose TBI given with or without alkylating agents may induce remissions in some patients with untreated CLL and NHL, 52,53 it has not been reported that low-dose TBI can induce CRs and molecular remissions in patients with chemotherapyresistant CLL, and in particular after failure of previous fludarabinecontaining regimens. Similarly, although low-dose TBI may have transient suppressive effects on CML, even high-dose myeloablative regimens (at least 1200 cGy TBI plus intensive chemotherapy) are by themselves often incapable of providing sustained disease control, as indicated by the frequent relapses observed after using T-cell-depleted allografts.…”
Section: Org Frommentioning
confidence: 99%
“…The overall response rate was around 85%. The complete remission rate occurred in 12.5% and 24.30% in the CLL and LG-NHL patients respectively [29].…”
Section: Discussionmentioning
confidence: 99%
“…In both NHL [10][11][12][13][14][15][16][17] and CLL [18][19][20], complete response (CR) rates of *25-80% have been observed depending on histology and whether the therapy was used as initial treatment. These studies have typically used 1.5 to 2.5 Gy in 10 to 20 fractions though in many cases, additional radiation to localized sites of disease following the TBI was utilized.…”
Section: Historymentioning
confidence: 99%